Quality Care Ambulance Services: Rohtak in Haryana, an eye opener - Kundan Mittal; Poonam Mehta; Anupama Mittal; Anindya Mittal (Wolters Kluwer Medknow Publications, 2018)
Objectives : To study the quality of ambulance services in medical emergencies at Pandit B D Sharma Institute of Medical Sciences, Rohtak, North India. Methodology: Type of study: Cross-sectional, by convenient sampling 50 people were included in the study. Data analysis was done by using Microsoft Excel 2007 version and proportions. Results: In present study it was seen that only 46% study subjects knew about the equipment's present in the ambulances, 54% have received a formal training before joining this occupation. emergency drugs were present in 94% ambulances. About 70% study subjects were aware of need for checking the expiry on drugs and only 48% of ambulances have extrication services. Conclusion : ambulance services are not up to mark and there is a wide scope of improvement for better delivery of health facilities to the people in India.